Effect of halogen addition to monolayer protected gold nanoparticles - Singh, Sanjay; Pasricha, Renu; Bhatta, Umananda M.; Satyam, P. V.; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2007)
The effects of N-halosuccinimide and halogen addition to monolayer protected gold nanoparticles (Au NPs) dispersed in organic media are described. Contrary to the expectation that nanoparticles dispersed in organic media are stable against aggregation, N-iodosuccinimide addition induced aggregation of octadecylamine capped gold nanoparticles in chloroform or toluene. It was observed that even KI and CuI addition could bring about the aggregation though they are very sparingly soluble in organic solvents. It was also found that even molecular iodine could bring about the above mentioned aggregation. Interestingly, when CuI is used the aggregated structures readily convert to very thin flat nanostructures upon exposure to an electron beam or UV irradiation. In fact when the aggregation is induced by the addition of KI or N-iodosuccinamide we do not see the flattening of the aggregated structures exemplifying the important role of Cu ions in making these flat structures.

Multiutility sophorolipids as nanoparticle capping agents: synthesis of stable and water dispersible Co nanoparticles - Kasture, Manasi; Singh, Sanjay; Patel, Pitamber; Joy, Pattayil Alias; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (Langmuir, 2007)
Sophorolipids are a class of glycolipids that can be obtained from fatty acids by simply treating them with yeast cells (Candida bombicola, ATCC 22214) and glucose. In this letter, we demonstrate the application of sophorolipids obtained from oleic acid as a capping agent for Co nanoparticles. Upon capping the nanoparticle surface, the sugar moiety of these sophorolipids is exposed to the solvent environment, making the nanoparticles stable and water-redispersible.

Nearly complete oxidation of Au(0) in hydrophobized nanoparticles to Au(3+) ions by N-bromosuccinimide - Singh, Sanjay; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2007)
Au degrees atoms in hydrophobized gold nanoparticles were oxidized to Au(3+) ions, nearly quantitatively, simply by treatment with N-bromosuccinimide and sonication. (1)H NMR results indicate that the octadecylamine molecules are detached from the Au degrees surface by NBS. The bromine molecules released by NBS are suggested to be the species responsible for the oxidation of Au degrees to Au(3+), which is supported by the observation that addition of molecular bromine also leads to similar results. A gratifying feature is that the Au(3+) ions could be subsequently reduced back to An nanoparticles.

Bacterial synthesis of copper/copper oxide nanoparticles - Hasan, Syed Saif; Singh, Sanjay; Parikh, Rasesh Y.; Dharne, Mahesh S.; Patole, Milind S.; Bhagavatula L. V. Prasad; Shouche, Yogesh S. (Journal of Nanoscience and Nanotechnology, 2008)
A bacterial mediated synthesis of copper/copper oxide nanoparticle composite is reported. A Gram-negative bacterium belonging to the genus Serratia was isolated from the midgut of Stibara sp., an insect of the Cerambycidae family of beetles found in the Northwestern Ghats of India. This is a unique bacterium that is quite specific for the synthesis of copper oxide nanoparticles as several other strains isolated from the same insect and common Indian mosquitoes did not result in nanoparticle formation. By following the reaction systematically, we could delineate that the nanoparticle formation occurs intracellularly. However, the process results in the killing of bacterial cells. Subsequently the nanoparticles leak out as the cell wall disintegrates. The nanoparticles formed are thoroughly characterized by UV-Vis, TEM, XRD, XPS and FTIR studies.
Keywords: bacterial synthesis; Nanoparticles; TEM; XPS; XRD

Bacterial synthesis of silicon/silica nanocomposites - Singh, Sanjay; Bhatta, Umananda M.; Satyam, P. V.; Dhawan, Alok; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2008)
The synthesis of silicon/silica nanoparticle composites by the bacterium Actinobacter sp. is demonstrated. More specifically, the formation of silicon/silica nanocomposite is shown to occur when the bacterium is exposed to K(2)SiF(6) precursor under ambient conditions. Based on the earlier reports where this bacterium has been shown to synthesize iron oxide and iron sulfide nanoparticles, it is hypothesized that this bacterium secretes reductases and oxidising enzymes, which lead to the Si/SiO(2) nanocomposite synthesis. The particles obtained by bacterial synthesis were thoroughly characterized. The cytotoxicity studies revealed that the particles do not display any cytotoxicity to human skin cells. The synthesis of silica nanoparticles by bacteria in the present study demonstrates the versatility of the organism, and the formation of elemental silicon by this environmentally friendly process expands further the scope of microorganism based nanomaterial synthesis.

Extracellular synthesis of crystalline silver nanoparticles and molecular evidence of silver resistance from morganella sp.: towards understanding biochemical synthesis mechanism - Parikh, Rasesh Y.; Singh, Sanjay; Bhagavatula L. V. Prasad; Patole, Milind S.; Sastry, Murali; Shouche, Yogesh S. (ChemBioChem, 2008)
There has been significant progress in the biological synthesis of nanomaterials. However, the molecular mechanism of synthesis of such bio-nanomaterials remains largely unknown. Here, we report the extracellular synthesis of crystalline silver nanoparticles (AgNPs) by using Morganella sp., and show molecular evidence I of silver resistance by elucidating the synthesis mechanism. The AgNPs were 20 +/- 5 nm in diameter and were highly stable at 1 room temperature. The kinetics of AgNPs formation was investigated. Detectable particles were formed after on hour of reaction, and their production remained exponential up to 18 h, and saturated at 24 h. Morganella sp. was found to be highly resistant to silver cations and was able to grow in the presence of more than 0.5 mm AgNO3. Three gene homologues viz. silE, silP and silS were identified in silver-resistant Morganella sp. The homologue of silE from Morganella sp. showed 99% nucleotide sequence similarity with the previously reported gene, silE, which encodes a periplasmic silver-binding protein. The homologues of silP and silS were also highly similar to previously reported sequences. Similar activity was totally absent in closely related Escherichia coli; this suggests that a unique mechanism of extracellular AgNPs synthesis is associated with silver-resistant Morganella sp. The molecular mechanism of silver resistance and its gene products might have a key role to play in the overall synthesis process of AgNPs by Morganella sp. An understanding of such biochemical mechanisms at the molecular level might help in developing an ecologically friendly and cost-effective protocol for microbial AgNPs synthesis.
Keywords: Biosynthesis; Morganella sp.; Nanoparticles; sil gene homologues; Silver

Silicate nanoparticles by bioleaching of glass and modification of the glass surface - Kulkarni, Sneha; Syed, Asad; Singh, Sanjay; Gaikwad, Anil; Patil, Kashinath; Vijayamohanan, K.; Ahmad, Absar; Ogale, Satishchandra (Journal of Non-Crystalline Solids, 2008)
Bioleaching is examined as a low temperature (50 degrees C) soft chemical approach to nanosynthesis and surface processing. We demonstrate that fungus based bioleaching of borosilicate glass enables synthesis of nearly monodispersed ultrafine (similar to 5 +/- 0.5 nm) silicate nanoparticles. Using various techniques such as X-ray diffraction, X-ray photoelectron spectroscopy and FTIR we compare the constitution and composition of the nanoparticles with that of the parent glass, and establish the basic similarities between the two. The bioleaching process is shown to enhance the non-bridging oxygen component and correspondingly influence the Si-O-Si network. The root mean square roughness of glass surface is seen to increase from 1.27 nm for bare glass to 2.52 nm for 15 h fungal processed case, this increase being equivalent to that for glass annealed at 500 degrees C. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Bioglass; Biomaterials; borosilicates; narroparticles

Direct method for the preparation of glycolipid-metal nanoparticle conjugates: sophorolipids as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles and their antibacterial activity - Singh, Sanjay; Patel, Pitamber; Jaiswal, Swarna; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2009)
The production of a new class of glycolipid-metal nanoparticle conjugates, namely, sophorolipid reduced/capped silver nanoparticles is demonstrated for the first time, by unveiling the reducing and capping abilities of sophorolipid derived from oleic acid. It is also demonstrated that the sophorolipid capped Ag nanoparticles are highly potent antibacterial agents, against both Gram-positive and Gram-negative bacteria. The utilization of sophorolipid brings out several advantages, such as eliminating the necessity for exogenous reducing agent and imparting better stability to the silver nanoparticles as compared to their oleic acid capped analogues. These sophorolipid capped silver nanoparticles can be obtained as a stable powder that can be re-dispersed in water as desired.

Effect of cultural conditions and media constituents on production of penicillin V acylase and CTAB treatment to enhance whole-cell enzyme activity of rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Singh, Sanjay; Poddar, Pankaj; Prabhune, Asmita; Pundle, Archana (Applied Biochemistry and Biotechnology, 2009)
Penicillin V acylase (PVA) is a pharmaceutically important enzyme as it plays a vital role in the manufacture of semi-synthetic beta-lactam antibiotics. Rhodotorula aurantiaca (NCIM 3425) produced high levels of intracellular penicillin V acylase after 18 h at pH 8.0 and temperature 27 degrees C. Fructose was the best carbon source for PVA production, whereas tryptone was the best nitrogen source to produce the enzyme up to 170 and 1,088 IU/l of culture, respectively. Additionally, the cell-bound PVA activity was enhanced on treatment with cationic detergent. Whole-cell activity was found to be doubled (204%) on treatment of 0.01 g dry weight of cells with 50 mu g/ml solution of N-cetyl-N,N,N-trimethylammoniumbromide at pH 8.0 for 1 h at room temperature. Atomic force microscopy images of permeabilized cells show perturbation in the cell wall and offer first-ever visual illustration of surface structure modifications that occur during permeabilization of R. aurantiaca cells leading to enhancement in activity of intracellular enzyme.
Keywords: Atomic force microscopy; Intracellular enzyme; Penicillin Vacylase; Permeabilization; Rhodotorula aurantiaca

Bacterial synthesis of phtocatalytically active and biocompatible TiO2 and ZnO nanoparticles - Singh, Sanjay; Britto, Virginia D.; Bharde, Atul A.; Sastry, Murali; Dhawan, Alok; Bhagavatula L. V. Prasad (International Journal of Green Nanotechnology: Physics and Chemistry, 2010)
TiO2 and ZnO nanoparticles are well known for their photocatalytic and ultraviolet (UV)-absorbent properties and have successfully entered into the market as consumer products. Large volume production of these nanoparticles by industries require environmentally friendly processes of synthesis. In this article, we show that when challenged with an appropriate precursor, the bacterium Actinobacter spp. can lead to the extracellular synthesis of ZnO and TiO2 nanoparticles. The biological way of synthesizing these materials probably leads to the in situ doping of elements like C, F, and N into their crystal lattices, which is evidenced by a red shift in the absorption edge. Because the doping is expected to affect the photocatalytic activity of these materials under different light conditions, such investigations have also been undertaken here. Further, the biocompatibility of these nanomaterials (cytotoxicity and genotoxicity) has also been investigated in detail.
Keywords: Biosynthesis; genotoxicity; Nanoparticles; Nanotoxicity; Photocatalysis

Cytotoxic and genotoxic assessment of glycolipid-reduced and -capped gold and silver nanoparticles - Singh, Sanjay; D'Britto, Virginia; Prabhune, Asmita; Ramana, C. V.; Dhawan, Alok; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
A systematic cytotoxic and genotoxic evaluation of glycolipid-conjugated silver and gold nanoparticles is carried out. These glycolipid nanoparticle conjugates are obtained by exploiting the reductive capability of a class of glycolipids called sophorolipids that play the role of capping agent as well. Further, when tested for their cytotoxicity and genotoxicity on HepG2 cells, these nanoparticles are found to be cytocompatible up to 100 mu M metal concentrations. Of the two metallic systems investigated, gold nanoparticles are found to be more cytocompatible than the same concentrations of silver nanoparticles. Similarly, it is also demonstrated that at 100 mu M, silver nanoparticles cause more DNA damage compared to gold nanoparticles of similar concentrations.

Vinylogous michael addition of 3-alkylidene-2-oxindoles to beta,gamma-unsaturated alpha-keto esters by bifunctional cinchona alkaloids - Jaiswal, Manish K.; Kumar, Rajesh; Singh, Sanjay; Jain, Shailija; Vanka, Kumar; Singh, Ravi P. (European Journal of Organic Chemistry, 2020)
A highly enantioselective vinylogous Michael addition of 3-alkylidene-2-oxindoles with beta,gamma-unsaturated alpha-keto esters using a bifunctional tertiary-amine thiourea catalyst is demontsrated. The challenging Michael reaction with the beta,gamma-unsaturated alpha-keto esters has been accomplished due to the synchronized H-bond guided dual activation of vinylogous nucleophile and electrophile by catalyst. The reaction afforded product in high yield while resulting in excellent stereocontrol (> 19:1E/Zand upto 99 %ee).
Keywords: 3-Alkylidene-2-oxindoles; Asymmetric synthesis; beta; gamma-Unsaturated alpha-keto esters; Michael adduct; Vinylogous Michael addition

Unlocking thermodynamic enolate for kinetically controlled desymmetrizing vinylogous (4+1) carbospiroannulation - Singh, Sanjay; Singh, Abhijeet; Pandya, Rinu; Vanka, Kumar; Singh, Ravi P. (Chemistry-A European Journal, 2025)
An unprecedented thermodynamically unfavorable (4+1) deysmmetrizing spiroannulation through a thermodynamic enolate intermediate, enabling a single-step synthesis of ubiquitous scaffolds such as all-carbon chiral spirocycles, is disclosed. In this spiroannulation, we present a vinylogous organocatalytic enantioselective desymmetrizing (4+1) cycloaddition approach involving alkylidene malononitrile and cyclopent-1,3-dienone. This carbospiroannulation method produces functionally enriched spiro[4,4]nonane structures with three stereocenters, has presented good-to-high yields and enantiomeric ratios. Detailed DFT calculations reveal an intriguing reaction mechanism, which validates our observations.
Keywords: 3-diones; alkylidene malononitrile; cyclopent-1; quaternary stereocenters; spiro compounds; thermodynamic enolate